2022
DOI: 10.3389/fgene.2022.824610
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Codon Bias in the Chloroplast Genomes of Theaceae Species

Abstract: Theaceae species are dicotyledonous angiosperms with extremely high ornamental and economic value. The chloroplast genome is traditionally used to study species evolution, expression of chloroplast genes and chloroplast transformation. Codon usage bias (CUB) analysis is beneficial for investigations of evolutionary relationships and can be used to improve gene expression efficiency in genetic transformation research. However, there are relatively few systematic studies of the CUB in the chloroplast genomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 53 publications
8
25
1
Order By: Relevance
“…Consequently, AT is strongly favored at the third bases of codons in the Saxifragales plastid genes, suggesting that selection pressure is responsible for the CUB patterns. Additionally, our findings revealed that ten genes in Saxifragales had GC1 > 0.5 and two genes had GC2 > 0.5, which is different from other studies where GC1, GC2, and GC3 values of plastid genes were all less than 0.5 [ 36 , 62 , 84 , 85 ]. Most notably, as proposed by Morton and So [ 86 ], stronger codon adaptation in plastid genes would lead to higher GC contents in the first and second bases of codons.…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, AT is strongly favored at the third bases of codons in the Saxifragales plastid genes, suggesting that selection pressure is responsible for the CUB patterns. Additionally, our findings revealed that ten genes in Saxifragales had GC1 > 0.5 and two genes had GC2 > 0.5, which is different from other studies where GC1, GC2, and GC3 values of plastid genes were all less than 0.5 [ 36 , 62 , 84 , 85 ]. Most notably, as proposed by Morton and So [ 86 ], stronger codon adaptation in plastid genes would lead to higher GC contents in the first and second bases of codons.…”
Section: Discussioncontrasting
confidence: 99%
“…In terms of nucleotide composition at three codon positions (GC1s, GC2s, and GC3s), together with the codon bias index N c and RSCU values, Quercus chloroplasts showed no significant differences between genomes but significant differences between genes within the genomes. Codon usage in chloroplast genomes of Theaceae species was found to be similar between species and prefer A/T ending codons [ 61 ], in accordance with the results of 16 Fagaceae chloroplast genomes [ 27 ] and the results of our investigation. We found that codon usage was consistent between oak chloroplast genomes, and that most A- and T-ending codons had relatively higher RSCU values and were therefore preferred for use.…”
Section: Discussionsupporting
confidence: 89%
“…This was consistent with previous studies. Chloroplast genomes in other plants, such as Camellia amplexicaulis [ 24 ], Panicum incomtum [ 25 ], Oryza australiensis [ 26 ], Euphorbia esula [ 27 ], etc., also tended to use codons ending with A/U. According to the RSCU analysis, it was found that most of the frequently used codons (RSCU > 1) were A/U-ending, whereas the less frequently used codons (RSCU< 1) were G/C-ending.…”
Section: Discussionmentioning
confidence: 99%